Havana: Youth, identity barriers, notes from social research - Peñate Leiva, Ana Isabel; López Santos, Dalgis (Última Década, 2020)
The present article considers some of the results of the investigation: «Youth Identity in different neighborhoods of the City of Havana», conducted by the authors in 2007 and is the second output of the project: «Territory and youth identity in Havana». In these pages the reader can approach some of the identity characteristics that distinguish youth living in five traditional districts of the Cuban capital, with its own characteristics and different in socioeconomic status: Náutica, Pogolotti, Jesús María, Guaicanamar and La Víbora. These districts commonly share a certain stability over time and the people living in them, which somehow determines the results, perhaps in other quarters a little more unstable or more intense flows, show different. However, the starting point is a brief tour of the forming process of the Cuban nation and nationality as well as a timely look at the history of the five districts which have been studied.